Skeletal outcomes of patients with osteogenesis imperfecta during drug holiday of bisphosphonates: a real-world study - Zhang, Yongze; Hu, Jing; Lin, Xiaoyun; Sun, Lei; Yan, Sunjie; Zhang, Qian; Jiang, Yan; Wang, Ou; Xia, Weibo; Xing, Xiaoping; Li, Mei (Frontiers in Endocrinology, 2022)
Purpose This study aimed to investigate the skeletal outcomes of patients with osteogenesis imperfecta (OI) who received bisphosphonates (BPs) treatment and entered drug holiday after achieving an age- and sex-specific bone mineral density (BMD) reference. Methods Patients with OI receiving BPs treatment were enrolled when they entered the drug holiday of BPs. The skeletal outcomes were evaluated in detail during the drug holiday, including BMD, X ray of bone, bone fracture incidence and bone turnover biomarkers. The pathogenic mutations of OI were identified by next-generation sequencing and confirmed by Sanger sequencing. Results A total of 149 OI patients (127 juveniles and 22 adults) were included, who entered the drug holiday after nearly four years of BPs treatment. Areal BMD at the lumbar spine increased from 0.934±0.151g/cm2 to 0.990±0.142g/cm2, and were stable in the second(1.029±0.176g/cm2) and third years(1.023±0.174g/cm2) of BPs drug holidays, and BMD at femoral neck, trochanter and total hip had no significant change, but it was gradually inferior to those of the same-gender juveniles in the second and third years of the drug holiday. BMD at lumbar spine and proximal hip did not change and were inferior to those of the same-gender adults. The average times of fractures fluctuated from 0.18 to 0.08 per year in juveniles while only one adult suffered from fracture during BPs drug holidays.Only a mildly high level of β-CTX of type 1 collagen in juvenile group. 17 patients received BPs retreatment because of bone loss during the drug holiday. OI type III and type IV and COL1A2 mutation were correlated to a longer duration of BP treatment to enter the drug holidays (all P < 0.05). Old age at initial treatment (OR, 1.056), and OI type III (OR, 10.880) were correlated to a higher risk of BPs retreatment. Conclusions OI patients will take nearly four years of BPs treatment to achieve the drug holidays. During the three years of drug holiday, the patient's BMD is stable and fracture incidence do not increase significantly. Late start of BPs treatment and more severe OI phenotypes are more inclined to need retreatment during the drug holiday.